Efficacy and Safety of Raltegravir-Based Dual Therapy in AIDS Patients: A Meta-Analysis of Randomized Controlled Trials - Huang, Yinqiu; Huang, Xiaojie; Chen, Hui; Wu, Hao; Chen, Yaokai (Frontiers in Pharmacology, 2019)
Background: The life expectancy for HIV-infected individuals has improved dramatically because of improvements in antiretroviral therapy (ART). Today simplified two-drug regimen enhances adherence and treatment satisfaction by reducing adverse effects. Therefore we need more evidence to show the benefits and risks of simplified ART regimen from RCTs. We try to compare the efficacy and safety between raltegravir-based simplified dual therapy (DT) with traditional triple therapy (TT) for people living with HIV/AIDS (PLWHA). Methods: We carried out a systematic review of randomized controlled trials (RCTs). Using a combination of key words “HIV”, “raltegravir”, and “protease inhibitor” in English electronic databases from Jan 1, 2004 to Jan 31, 2018, we pooled data across studies and estimated summary effect sizes by Review Manager (version 5.3). Results: We included eight RCTs involving 4420 PLWHA, 2187 (49.5%) receiving raltegravir-based simplified DT and 2144 (48.5%) traditional TT. The proportion of viral suppression was 79% at 48 weeks, 74% at 96 weeks in simplified regimen while 78% at 48 weeks, 71% at 96 weeks in traditional NRTIs-based regimen group. Furthermore, the proportion of viral suppression in raltegravir-based DT was greater than that of TT group at 24 weeks (risk ratio 1.11, 95% credible interval 1.02-1.21; p=0.01). The significantly higher CD4 cell counts than those receiving traditional NRTIs-based three-drug regimen at 48 weeks and 96 weeks. As for adverse events and mortality rates, DT was similar with TT group. However, raltegravir-based DT had better adherence compared with NRTIs-based TT. Conclusion: We found raltegravir-based simplified regimen were non-inferior to NRTIs-based regimen in viral suppression. Furthermore, simplified regimen had better CD4 cell count and lower adverse events.